JURIDICAL REVIEW ON CHANGES TO AD/ARTS OF SUBUR MAKMUR AGRO INDUSTRY COOPERATIVE REGENCY EAST KUTAI POST-CANCELLATION - Esti Royani; Khoirul Arifin; Hagverdiyeva Shalala (Sekolah Tinggi Ilmu Hukum Awang Long, 2023)
Amendments to the Cooperative Law brought Number 25 of 1992 to Number 17 of 2012 bringing a very basic change, this is due to the change in cooperative business from being member welfare to corporations, and then canceled by the Constitutional Court. This is what makes the author interested in conducting research so that the author takes the title of Juridical Review of Changes in Ad/Art of Subur Makmur Agro-Industry Cooperatives, East Kutai Regency after the Cancellation of Law Number 17 of 2012 concerning Cooperatives by the Constitutional Court. From the research conducted, finally the author can conclude that with the cancellation of the entire contents of the operation law number 17 of 2012 by the Constitutional Court with the decision number: 28/PUU-XI/2013 which states cancel the entire contents of the law number 17 of 2012 and at the same time re-enacting Law No. 25 of 1992 until the next cooperative law, then legally all cooperative legalities (AD/ART) that rely on law number 17 of 2012 are null and void and return to the law. The Legality of Cooperatives (AD/ART) which relies on the cooperative law number 25 of 1992, is the case with the Subur Makmur Agro-Industry Cooperative, Sangatta, East Kutai Regency.